The Effect of Different Storage Conditions for Refilled Plastic Drink Bottles on the Concentration of Microplastic Release in Water - Hadeed, Mustafa Dheyaa Mohamed; Al-Ahmady, Kossay Kamalaldeen (Journal for Research in Applied Sciences and Biotechnology, 2022)
The demand for water consumption in plastic bottles has increased in recent years. Most consumers of this type of water think that it is well sterilized. This is due to the high level of propaganda that accompanies its production regarding the extent of its validity. It is also common to reuse these bottles for several times by filling it frequently for different uses, and their use for preserving and storing different types of liquids. This study is conducted for the purpose of detecting and evaluating the pollution caused by microplastics in plastic bottles filled with water for one time, as well as water bottles reused more than once. Moreover, it evaluates the effect of storage period and conditions on the abundance of microplastics when bottles are stored for different times and under the influence of different conditions (shade, cooling and freezing). The results of the study show the presence of fine microplastics in open bottled water exposed to different storage conditions. The highest concentration of microplastics is obtained in storage conditions under the influence of shade with a limit of (1050) microplastics / liter, while the lowest concentration is obtained at around (20) microplastics / liter. The highest concentration of microplastics is obtained in storage conditions under the influence of cooling, with a limit of (850) microplastics / liter, whereas, the lowest concentration is obtained in the range of (16) microplastics / liter. Under the influence of freezing, the highest concentration of microplastics is obtained in the range of (648) microplasics / liter, while the lowest concentration Is obtained in the range of (20) microplastics / liter. Through the results, it is noted that there is a noticeable gradient in the concentration of microplastics for the samples that have been studied. It is also noted that there is an increase in the concentration of microplastics with repeated reuse during continuous periods of time. It is recommended that more studies and research be conducted indicating the extent of the impact of microplastics on human health in addition to other environmental components with emphasis on finding treatment means to get rid of microplastics.